The Nova Scotia Labour-Management Agreements - Henson, Guy (Relations industrielles / Industrial Relations, 1969)
The Nova Scotia Joint Labour-Management Study Committee was established in May 1962. The present paper will attempt to give an account of the Committee's origins, accomplishments to date, and present activities and objectives ; methods or processes of work and some assessment of its significance.